Collective Pitch Control of Wind Turbines using Stochastic Disturbance Accommodating Control - Girsang, Irving Paul (2016)
Fidelity of a plant's dynamic model is a concern in any controller design process. In this context, fidelity refers to which dynamics of the plant needs to be included in the control model and which dynamics can be left out or approximated. Studies on wind turbine control have shown that modelling error due to the unmodeled dynamics can lead to unstable closed-loop dynamics. This paper investigates the use of Kalman estimator to design the Stochastic Disturbance Accommodating Control (SDAC) scheme to stabilize the system in the presence of the unmodeled dynamics. Performance of the presented control scheme is investigated through simulations on two different wind turbine configurations under turbulent wind conditions with different mean wind speeds and turbulence intensities using FAST (Fatigue, Aerodynamics, Structures, and Turbulence) aero-elastic tool. The generator speed regulation, drivetrain load, and control effort of the presented control scheme are compared with those of the baseline Gain Scheduled Proportional Integral (GSPI) controller. The results indicate better speed regulation and lower drivetrain load for the presented SDAC under the tested wind conditions.